Unleashing The Power of Big Data: The Phenomenon Behind Indonesia's Smart City Policy Implementation - Ikhwan Rahmatika Latif; Ikhsan Ikhsan; Vellayati Hajad; Arif Akbar; Afrijal Afrijal; Ilham Mirza Saputra (Kybernology : Journal of Government Studies, 2023)
The concept of smart cities has emerged as a promising prospect for several major urban centers in Indonesia. Putting smart city projects together requires thinking about many things. Big data has become one of the most important parts for making sure that these projects will last. Employing big data technology makes it easier to improve the ways that data is stored and processed. This makes it possible to gather useful data that could greatly improve a wide range of smart city services. This study uses a library-based qualitative research approach to analyze scholarly journals and relevant literature. The method involves meticulous collection of data from carefully chosen libraries, aiming to provide comprehensive insights into the phenomenon of big data in smart cities implementation within government administration. This study aims to contribute to the identification and analysis of challenges encountered in emergency situations, with the ultimate goal of providing assistance in effectively mapping the problem at hand. The present discourse underscores the indispensability of Indonesia's contemporary human mindset in bolstering the viability of the smart city paradigm.